Gambaran Pengetahuan Remaja Putri Mengenai Penanganan Dismenorea Di Kelurahan Kedungwinong - SANDRA, GHOZALI BINTANG; , Winars ih Nur Ambarwati, S.Kep.,Ns, ETN, M.Kep; , Sri Enawati S .Kp., M.Kes (2015)
Dysmenorrhoea is pain arising during menstruation in young women that can interfere with daily activites, include they could not go to school. Knowledge is the result of "know" and this happened after people perform sensing on a particular object. Knowledge about dysmenorrhoea could influence how they should do when they were dismenorea. The preliminary study results many girls still know yet about dismenorea and dysmenorrhoea handling. The purpose of this study was to know descriptive of knowledge adolescent girls about dysmenorrhoea handling at Kedungwinong village. Research method was descriptive analytic. Sample are 62 adolescent girls in Kedungwinong village with 10 up to 19 year old, has had of menstruation and live in Kedungwinong village. Taking sample was using proportional sampling technique. Instrument research was using questionnaire after do validity and reliability test. Data analysis was using descriptive of questionnaire and using percentage. The results study was 10 respondents (16,1%) with good knowledge, 34 of respondents ( 54,8 %) with fair knowledge, and 18 respondents ( 29 %) with less knowledge. Reducing pain of dysmenorrhoea of respondents they were 74,2% were drinking warm water.